Aligning implementation research and clinical operations: a partnership to promote implementation research in primary care - Anita D Misra-Hebert; Valerie Chepp; Steven Masiano; Mario Scarcipino; Audrey Hudak; Eva Steinel; Christopher Babiuch (BMJ Open Quality)
The rigorous evaluation of the implementation of evidence into routine practice in a health system requires strong alignment between research and clinical operational teams. Implementation researchers benefit from understanding operational processes and contextual factors when designing data collection while operational teams gain an understanding of implementation frameworks and outcomes using both qualitative and quantitative data. However, interventions to build capacity for these evaluation partnerships—particularly those tailored for clinical operational practitioners—are limited. We developed a model for a research–clinical operational partnership to build capacity for rigorous implementation evaluation. The model incorporated didactic and interactive education alongside small group discussion. Using reflective qualitative analysis, we show how the year-long partnership resulted in an effective collaboration that built capacity for rigorous operational evaluation, informed plans for data collection to include provider and patient barriers to adoption and increased awareness of implementation cost barriers. Improved capacity for implementation evaluation was demonstrated by the knowledge acquisition that resulted for both teams as a result of the collaboration and the education that penetrated to other aspects of the operational team’s work beyond the immediate project. Programme successes and improvement opportunities were also identified. The partnership model shows how a formal research–clinical operational collaboration can build capacity for rigorous implementation evaluation and close the gap between implementation researchers and practitioners in a large health system. While larger-scale process evaluation is common, creating space for project-specific capacity-building initiatives, with varying levels of research involvement, can also advance the field of implementation science, offering new perspectives and partnerships, as well as opportunities to advance learning even for smaller-scale evidence translation.